An Ontology of City, Art, and Time: Plotting the Work of Fra Paalman - Paalman, Floris (FRAME, Journal of Literary Studies, 2026)
This article examines the artistic work and practice of Fra Paalman in order to rethink the relationship between art and the urban environment. It attempts to move away from the concept of urban art as capturing a fragment of a certain time and place in a city, given how such theoretical frameworks always imply a sort of ‘ideal city,’ or an imagined wholeness. Instead, Paalman’s art is explored for how the city becomes spatially integrated into, and temporally traversed by, the artwork, and vice versa. Through this, the article uses Paalman’s artwork to demonstrate how urban ontology is temporal, and acts as a composite and integration of various levels of experience.